Simulation of two phase oil-gas flow in T-junction - Sam, B. (Asian Research Publishing Network, 2016)
T-junction, or commonly known as stand pipe appendage, is used by oil/gas industries to tap gas from existing production header for the purpose of downstream pipeline instrumentation. The appendage is either pre-design or retrofitted with minimum internals for maximum reliability for remote deployment. The motivation for this research originated from the lack of stand-pipe design method to correctly account for the separation of multiphase fluid at the T-junction. Consequently, sizable amount of liquid holdup occurs in the side arm, resulting in the so-called carryover issue. This situation is further aggravated by the different flow regimes in the production header which are not taken into account by the design practice. The negative consequences of this carryover on the operation of downstream unit have often led to frequent trip and maintenance issues. This paper presents the finding of the two phase oil/gas separation in T-junction using a simplified one-dimensional model. The effect of operating pressure, gas-oil ratio (GOR), oil flow rate and arm length on gas fraction in side arm is reported. The computed solutions are compared with experimental data and a good agreement is achieved. The results show that operating pressure is the most influential parameter in ensuring efficient separation. Â©2006-2016 Asian Research Publishing Network (ARPN).